Haemodialysis and ultrafiltration in babies weighing under 1000 g. Issue 3 (November 1995) - Coulthard, M. G.; Sharp, J.
Abstract : Until now it has not be feasible to haemodialyse babies with renal failure who weigh less than 1000 g. Three babies weighing 630, 808, and 1140 g are described. They had multiorgan failure and could not be peritoneally dialysed. They were treated with veno-venous ultrafiltration and haemodialysis using a manual syringe driven technique that required only simple equipment. This method is highly labour intensive, but can provide control of fluid volume and plasma biochemistry in these very sick infants. Their prognosis, however, is determined by the underlying cause of their renal failure, and remains poor.